Integrating experimental model, LC-MS/MS chemical analysis, and systems biology approach to investigate the possible antidiabetic effect and mechanisms of Matricaria aurea (Golden Chamomile) in type 2 diabetes mellitus - Ismail, Yassin; Fahmy, Dina M.; Ghattas, Maivel H.; Ahmed, Mai M.; Zehry, Walaa; Saleh, Samy M.; Abo-elmatty, Dina M. (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) is a heterogeneous disease with numerous abnormal targets and pathways involved in insulin resistance, low-grade inflammation, oxidative stress, beta cell dysfunction, and epigenetic factors. Botanical drugs provide a large chemical space that can modify various targets simultaneously. Matricaria aurea (MA, golden chamomile) is a widely used herb in Middle Eastern communities for many ailments, including diabetes mellitus, without any scientific basis to support this tradition. For the first time, this study aimed to investigate the possible antidiabetic activity of MA in a type 2 diabetic rat model, identify chemical constituents by LC-MS/MS, and then elucidate the molecular mechanism(s) using enzyme activity assays, q-RTPCR gene expression analysis, network pharmacology analysis, and molecular docking simulation. Our results demonstrated that only the polar hydroethanolic extract of MA had remarkable antidiabetic activity. Furthermore, it improved dyslipidemia, insulin resistance status, ALT, and AST levels. LC-MS/MS analysis of MA hydroethanolic extract identified 62 compounds, including the popular chamomile flavonoids apigenin and luteolin, other flavonoids and their glycosides, coumarin derivatives, and phenolic acids. Based on pharmacokinetic screening and literature, 46 compounds were chosen for subsequent network analysis, which linked to 364 candidate T2DM targets from various databases and literature. The network analysis identified 123 hub proteins, including insulin signaling and metabolic proteins: IRS1, IRS2, PIK3R1, AKT1, AKT2, MAPK1, MAPK3, and PCK1, inflammatory proteins: TNF and IL1B, antioxidant enzymes: CAT and SOD, and others. Subsequent filtering identified 40 crucial core targets (major hubs) of MA in T2DM treatment. Functional enrichment analyses of the candidate targets revealed that MA targets were mainly involved in the inflammatory module, energy-sensing/endocrine/metabolic module, and oxidative stress module. q-RTPCR gene expression analysis showed that MA hydroethanolic extract was able to significantly upregulate PIK3R1 and downregulate IL1B, PCK1, and MIR29A. Moreover, the activity of the antioxidant hub enzymes was substantially increased. Molecular docking scores were also consistent with the networks’ predictions. Based on experimental and computational analysis, this study revealed for the first time that MA exerted antidiabetic action via simultaneous modulation of multiple targets and pathways, including inflammatory pathways, energy-sensing/endocrine/metabolic pathways, and oxidative stress pathways.